Quality management and profitability linkage: Does the length of QM adoption act as the moderating variable? - Agus, Arawati (Universiti Utara Malaysia, 2008)
Manufacturing companies in Malaysia have never had it so tough. They are now confronting increasing prices of oil and raw materials, high advancement in innovation and technology, as well as high customer expectation on the quality of products and services. In addition, managers of these companies are well aware of the increasing competitive pressures in the world market. It is clear today that these pressures are due largely to the increased performance of those firms that have successfully implemented quality improvement.This paper presents the findings from an empirical study examining the relationship between quality management (QM) practices and profitability in the electronics and electrical industry in Malaysia. It is said that QM has the potential to not only enhance production efficiency and effectiveness, but also improves bottom-line results. Much has been written about the relationship between QM and performance. However, the link of QM practices to profitability in the electronics and electrical industry in Malaysia has not been fully addressed in empirical studies. To address this issue, this paper investigates the impact of QM practices on profitability in the Malaysian electronics and electrical industry using correlation, multiple regression,and hierarchical regression analyses. The findings revealed that quality measurement, supplier relations, and benchmarking in particular, appear to be of primary importance and exhibit significant impact on profitability. Findings of the study provided a striking demonstration of the importance of implementing effective QM practices for the electronics and electrical industry in Malaysia in enhancing its profitability. However, the study failed to provide the statistical evidence of the existence of the moderating effect of the length of QM adoption on the QM and profitability linkage.